Prototype Setrika dan Pelipat Pakaian Otomatis Berbasis Microcontroller - Muhamad Ariandi; Muhammad Iqbal Triyadi (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
Improving efficiency and quality in ironing and folding clothes is a primary concern in modern households. This research aims to develop a prototype of an automatic ironing and folding device that enhances productivity while reducing processing time compared to manual methods. Testing was conducted on three types of fabric materials: polyester, cotton, and linen, by comparing time and folding quality between the automatic and manual methods. The results showed that the automatic prototype completed the process in an average of 5 minutes for all fabric types, compared to 8 minutes with the manual method. In terms of folding quality, the automatic prototype demonstrated more consistent results with a high level of neatness across all fabric types. The conclusion of this study is that using the automatic ironing and folding prototype provides significant time efficiency and improves quality compared to the manual method. These findings contribute to the development of more effective and efficient household technologies.